Application of Biology Learning Media at SMA Negeri 3 Samarinda Using the Direct Instruction Model to Improve Student Learning Outcomes - Halim, Soesilowaty (PT Literasi Nusantara Publisher, 2022)
The study of biology through instructional media and the Direct Instruction Model has been implemented and tested on 30 students of class XI of SMAN 18 Samarinda using a one-group pretest-posttest design. The purpose of this study is to improve student learning outcomes. Data were analyzed by descriptive qualitative, the results as follows: very well performed learning; activities of students is too good; increaseing the students’ learning outcomes and all students give good responses to the instructional media and application. The conclusions of this study is that the application of instructional media using Direct Instruction models can improve student learning outcomes.